Successful Surgical Treatment of Postinfarction Rupture of Left Ventricular Myocardium - M. K. Mazanov; N. I. Kharitonova; A. A. Baranov; S. Yu. Kambarov; N. M. Bikbova; M. G. Ivanov; A. G. Harutunyan (Неотложная медицинская помощь, 2020)
ABSTRACT. The rupture of the left ventricle free wall is one of the most dangerous complications of myocardial infarction. Due to the widespread availability of echocardiography method, the detection of this fatal complication and the number of lives saved after surgery grew. The survival of patients depends on early diagnosis, stabilization of the patient’s condition, promptness and tactics of surgical intervention. We report a case of successful closure of a rupture of the left ventricle free wall on the 15th day after myocardial infarction.